FRAMING CULTURE THROUGH LANGUAGE: A DISCOURSE ANALYSIS OF POETRY LEARNING VIA TELEGRAM BOT IN DELI MALAY CLASSROOMS - Paino, Novhira Putri; Adisaputera, Abdurahman; Lubis, Malan; Lubis, Joharis; Dalimunthe, Syairal Fahmy; Harahap, Safinatul Hasanah (ppjbsip, 2025)
This study explores the integration of digital technology and local wisdom in Indonesian poetry education through Telegram BOTs, reframed from a discourse analysis perspective. Conducted at SMA Negeri 1 Hamparan Perak, the study investigates how students engage with poetry that embodies the cultural values of the Deli Malay community using interactive Telegram-based learning modules. A mixed-methods approach was applied, combining tests, questionnaires, interviews, and classroom observations. Quantitative results show significant improvement in students’ literary understanding and creative writing skills. Qualitatively, students expressed higher interest and motivation when the content related to their heritage. From a discourse analysis viewpoint, the study highlights how Telegram BOTs act as narrative agents, delivering, structuring, and mediating meaning through localized poetic texts. Students' responses reveal not only improved comprehension but also an evolving use of cultural discourse, including metaphors, proverbs, and references to regional customs. The learning process became an interactive dialogue between digital technology and traditional values, fostering identity construction and reflective thinking. Teachers also used culturally rooted language frames to scaffold understanding, such as embedding moral themes in poetry discussions. This study recommends shifting poetry learning from merely structural analysis to discourse-sensitive methods, focusing on how language shapes thought, identity, and social cohesion. The findings suggest that culturally integrated BOTs are not only pedagogically effective but also discursively powerful tools for literacy and civic education in multicultural contexts.